SOCIAL MEDIA MARKETING STRATEGIES IN BUILDING BRAND ENGAGEMENT IN FOOD & BEVERAGE COMPANIES (CASE STUDY AT PT MODULAR KULINER INDONESIA) - Caroline, Ivana; Susanto, Denies (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to explore the social media marketing strategy implemented by PT Modular Kuliner Indonesia (Hangry) in building brand engagement for their brands, such as Ayam Koplo, Ayam Goreng Bu Tumbar, and UNO Chicken. Along with the advancement of technology and changing consumer behavior, which increasingly relies on social media, the company leverages digital platforms to reach a wider audience and enhance consumer engagement. This research uses a qualitative approach with a case study method, including document review, in-depth interviews, and participatory observation to gain deeper insights into the digital marketing strategies used by Hangry. The results of the study show that social media, particularly platforms like Instagram, plays a crucial role in building brand engagement for Hangry. Hangry Indonesia has successfully utilized social media to increase brand awareness and engagement with their audience. This is reflected in the significant increase in views and accounts reached. For example, in March 2025, the number of views reached 662,805, with 377,936 accounts reached, the majority of which were non-followers (95.6%). In April 2025, the number of views rose to 1,334,266, with 712,845 accounts reached, and the percentage of non-followers increased to 97.3%, indicating that the advertising campaigns and content strategies implemented were highly effective in expanding audience reach. By utilizing attractive and relevant content, Hangry has been able to create more intense interactions with their audience, resulting in increased brand awareness and customer loyalty. Collaboration with influencers and external parties in marketing campaigns has also proven effective in expanding market reach and strengthening consumer engagement. On the other hand, the use of analytical tools to monitor social media content performance has allowed Hangry to adjust strategies in real-time, improving the effectiveness of the campaigns executed. However, this study also identifies some challenges faced by Hangry in implementing their social media marketing strategy, such as the management of more varied content and the exploration of new social media platforms to further increase engagement. This research provides valuable insights into how the cloud kitchen business model can utilize social media marketing to strengthen long-term relationships with customers in the increasingly competitive food and beverage industry.